Firms and Trade on the Island of Ireland - Lawless, Martina (Statistical and Social Inquiry Society of Ireland, 2019)
This paper documents the broad patterns of firm sales and participation in trade for Northern Ireland and Ireland. Looking across sectors and firm size groups, it examines the distribution of cross-border trade with a particular focus on the degree of integration of supply chains. Using both aggregate and firm-level data, this paper aims to give as comprehensive a picture as possible of the international activities of firms in both economies. I highlight the contribution made by micro and small firms in cross-border trade. Despite a steadily increasing probability of being an exporter as firm size increases, cross-border trade has many features that make it resemble local trade rather than international export activity. Trade in intermediate products and the large role of two-way traders shows that supply chain links are a major element of cross-border trade.
(read before the Society, 25 April 2019) Symposium: The Economies on the Island of Ireland
Keywords: export participation; cross-border trade; supply chains; 314.15